A New Secret of the Youth Olympic Games: A Model for Olympic Facilities Reform - Jeffrey Petersen; Lawrence W Judge (Journal of Applied Sports Management, 2023)
The authors center their attention on Olympic venues and the Youth Olympic Games (YOG), arguing that a new reform model for Olympic venues should be based on the model of the YOG. Although the focus of the proposed reform model remains on venue reform, the authors also considers all four elements from Müller’s (2015) mega-events definitional model. These elements include visitor attractiveness (tickets sold), mediated reach (broadcast rights fees), cost (total cost), and transformation (capital investment). The reform model is argued to improve the overall cost and long-term impact of Olympic Games infrastructure, making it more manageable and sustainable.
Keywords: Facility Design; Operation Management; Sport Facilities; Venue; YOG